2021
DOI: 10.3390/ani11020279
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Mastitis Pathogens—Epidemiological Investigations of a Pseudomonas aeruginosa Mastitis Outbreak in an Austrian Dairy Herd

Abstract: The present study describes an outbreak of Pseudomonas (P.) aeruginosa mastitis in a 20-cow dairy herd where throughout genotyping of isolates reusable udder towels were identified as the source of infection. Sampling of cows during three herd surveys and bacteriological culturing showed that P. aeruginosa was isolated from nine cows with a total of 13 infected quarters. Mastitis occurred as mild clinical or subclinical infection. P. aeruginosa was additionally isolated from a teat disinfectant solution, conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In recent years, the incidence of clinical mastitis due to P. aeruginosa and the associated risk of large economic losses have increased in large dairy herds, causing significant problems for affected farmers (Kawai et al, 2017;Klaas and Zadoks, 2018). Consistent with the previous issue, our study found that P. aeruginosa might become the major pathogenic bacterium that survives on the milk or udder surface of cows with mastitis (Kawai et al, 2017;Schauer et al, 2021). Notably, all five P. aeruginosa isolates from these cows were MDR.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, the incidence of clinical mastitis due to P. aeruginosa and the associated risk of large economic losses have increased in large dairy herds, causing significant problems for affected farmers (Kawai et al, 2017;Klaas and Zadoks, 2018). Consistent with the previous issue, our study found that P. aeruginosa might become the major pathogenic bacterium that survives on the milk or udder surface of cows with mastitis (Kawai et al, 2017;Schauer et al, 2021). Notably, all five P. aeruginosa isolates from these cows were MDR.…”
Section: Discussionsupporting
confidence: 88%
“…Co-infection might be clarified as that either one organism was the etiological agent, and the rest were commensals, or one organism stimulated primary infection, and the rest were secondary invaders. The great incidence of co-infections in our investigation could be attributed to the inadequate typical sanitary and managemental routines, comprising overcapacity, and insufficient dung elimination within the dairy farms which allowed the expand of environmental and contagious infections (Rahularaj et al 2019;Schauer et al 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Despite the lower number of isolates, some of the isolated bacteria have medical and veterinary interests, such as Escherichia coli, Serratia marcescens, Klebsiella pneumoniae, and Pseudomonas aeruginosa, which may be involved in several diseases such as diarrhea (Dubreuil et al 2016), mastitis (Schauer et al 2021;Zaatout, 2021), and urinary tract infections (Su et Finally, the logistic regression models showed interesting insights. For C. freundii, Sampling Area 2 (compared to Sampling Area 1) was a protection factor and the presence of wounds was a risk factor.…”
Section: Discussionmentioning
confidence: 99%